2001
DOI: 10.1002/pd.69
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Y chromosome‐specific DNA in the plasma and urine of pregnant women using nested polymerase chain reaction

Abstract: The present study was undertaken to evaluate a nested polymerase chain reaction (PCR) for detection of Y chromosome-specific fetal DNA in maternal plasma and urine of pregnant women during different gestational stages. DNA isolated from plasma and urine samples of 80 pregnant women (between 7 and 40 weeks' gestation) underwent amplification for Y chromosome-specific 198 bp DNA by nested PCR. The postpartum analysis of fetal gender showed that 55 women carried male and 25 female fetuses. Among the 55 women bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
2
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 8 publications
2
39
2
1
Order By: Relevance
“…Therefore, from the 57 selected studies used in the meta-analysis, we extracted 80 data sets 37,56,57,60,61,67, 77. † References 6,[14][15][16][17]23,25,27,55,59,62,70,75,78,88. (eTable 2).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, from the 57 selected studies used in the meta-analysis, we extracted 80 data sets 37,56,57,60,61,67, 77. † References 6,[14][15][16][17]23,25,27,55,59,62,70,75,78,88. (eTable 2).…”
Section: Study Selectionmentioning
confidence: 99%
“…35,49,60 The remaining 4 data sets 14,15,79 showed poor and inconsistent performance (sensitivity: 6.3%, 32.3%, 38.2%, and 95.1%; specificity: 98.2%, 98.2%, 96%, and 87.9%; and PPV, 90.7% and NPV, 52.4% [across the 4 data sets]). The high specificity is likely an artifact; if no fetal DNA can be amplified, the test will not produce false-positive results.…”
Section: Sample Typementioning
confidence: 99%
See 1 more Smart Citation
“…However, maternal urine analysis was faced with technical difficulties, and it was suggested that the concentration of transrenal DNA might be too low for standard PCR protocols. On the basis of DNA isolation and amplification techniques some authors reported positive results (2,(5)(6)(7), whereas others did not (4,8,9 ). The reason for the differing outcomes was attributed to renal function, in particular glomerular permeability, small size of DNA fragments, and the presence of urinary nucleases.…”
mentioning
confidence: 99%
“…Otherwise, it is difficult to explain how fetal DNA appears in the urine of pregnant women or how tumor-specific DNA markers appear in the urine of patients with tumors located outside of the urinary system. This original observation was reproduced in many laboratories (2)(3)(4)(5)(6)(7). At the same time, several groups could not detect fetal DNA in the urine of pregnant women (8,9 ), raising doubts about the concept of Tr-DNA.…”
mentioning
confidence: 99%